Cross Stitch Dinosaurs and Monsters - Greenoff, Jane (David & Charles Book, 1994)
Be on the lookout for a terrible T-Rex, a cross crocodile, a grumpy spider, the terror-bird, the vampire bat, and 5 more.
Keywords: Crafts & Hobbies; Cross-Stitch; Needlework